The Grave as a Doorway to the Other World Architectural Religious Symbolism in Iron Age Graves in Scandinavia - Nordberg, Andreas 1971- (2009)
During the last twenty years, the category ‘grave’ has been the subject of increasing debate in Swedish archaeology. It has been recognized that monuments commonly regarded as graves are sometimes also found in cultic contexts other than those associated with death and burial. In many cases, for instance, monuments similar to graves have been erected at cult sites, and seem to have been used in sacrificial practices rather than for burials. According to archaeological, textual and onomastic sources, it was common practice in Old Norse religion to suspend sacrificial victims from trees of from upraised posts, or to deposit offerings at the base of sacred rocks and boulders. In all these cases, the trees, posts and boulders seem to be representation of the World Axis, depicted in cosmological myths as a Cosmic Tree, Pillar or Mountain. I argue that these various representations of the World Axis are also incorporated in the architectonic symbolism of several forms of grave monuments in pre-Christian Scandinavia. The architectonic shape of these monuments could thus be used in several different contexts, since they represented a ‘Cosmic Center’ and a ‘doorway’ to the Other World.
Keywords: Cosmic Center; World Axis; architectonic symbolism; Burial; cult site; Grave